Prototype aircraft development trials with particular reference to tropical trials - Keshu, S. C. (Defence Science Journal, 2014)
Flight development trials on prototype aircraft play a vital part in the design and development programme of a new aircraft and facilitate the introduction of the aircraft for operational use in Air Force Squadrons. The facilities required for such flight testing, the training of technical personnel and the organization of a flight test center are briefly described.